The urgency of digital technology in education: a systematic literature review - Putra, Johni Eka; Sobandi, A; Aisah, Aisah (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
The research objective is to investigate the urgency, impact, efforts, and challenges in integrating digital technology in education in Indonesia, with a focus on improving the quality of learning, reducing gaps in educational access, and preparing students to face a future integrated with technology. This research uses the Systematic Literature Review (SLR) method with 171,000 articles from Scopus, ERIC and Google Scholar sources (2018-2024 period), using the keyword